2023
DOI: 10.21014/actaimeko.v12i4.1646
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance analysis between two different generations of an automatic milking system

Maria Teresa Verde,
Roberta Matera,
Francesco Bonavolonta
et al.

Abstract: The adoption of Automatic Milking Systems (AMS) in Europe and Italy has been increasing gradually in recent years, driven by the advantages they offer over traditional milking methods. AMS reduces the need for manual labor, increases milk production, standardizes teat cleaning and disinfection, and promotes animal welfare. The adoption of milking robots also allows for continuous monitoring of milk parameters, animal health status, and production performance. In a recent study, the authors analyzed the improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…With the proliferation of Internet of Things (IoT) devices, safeguarding sensitive data has become paramount. As highlighted by the recent literature [1], many of these data are measurements, and the IoT paradigm is the basis of modern distributed measurement systems (DMSs), used for the monitoring of many heterogeneous physical quantities, crucial for wellness [2,3], industrial automation, education, power generation and distribution, smart agriculture, and farming [4,5], but also for the safety of people [6][7][8] and structures [9]. The cyber security company Check Point Research has reported a significant surge in cyber attacks targeting IoT devices during the current calendar year.…”
Section: Introductionmentioning
confidence: 99%
“…With the proliferation of Internet of Things (IoT) devices, safeguarding sensitive data has become paramount. As highlighted by the recent literature [1], many of these data are measurements, and the IoT paradigm is the basis of modern distributed measurement systems (DMSs), used for the monitoring of many heterogeneous physical quantities, crucial for wellness [2,3], industrial automation, education, power generation and distribution, smart agriculture, and farming [4,5], but also for the safety of people [6][7][8] and structures [9]. The cyber security company Check Point Research has reported a significant surge in cyber attacks targeting IoT devices during the current calendar year.…”
Section: Introductionmentioning
confidence: 99%